Research of a Frequency Magnetic Converter on the Basis of Transistor Structure with Negative Resistance - Osadchuk, S. V.; Osadchuk, V. A. (Elektronika ir Elektrotechnika, 1999)
There is presented a mathematical model of a magnetic frequency converter on the basis of structure of bipolar and field-effect transistors with negative resistance. Outgoing from the model, there is obtained the equation of conversion, which describes dependence of a resonance frequency on a magnetic strength. The experimental and theoretical dependencies of the equation of conversion are shown.